Implementation of Active Knowledge Sharing Strategy in Improving Arabic Writing Skills of Class X Students at Al-Ikhlas Islamic Boarding School Al-Ikhlas Ad-Dary DDI Takkalasi - Nur Asya, Said Salihin; Saepudin; Herdah (Al-Iftah: Journal of Islamic studies and society, 2022)
The Arabic language learning strategy is a series of efforts made by the Arabic teacher to make the learning process run according to predetermined concepts. The concept that must be created by the teacher is learning that is effective, communicative, efficient, fun, innovative, and quality. To improve the development of learning Arabic in educational institutions, it is necessary to create innovative strategies from Arabic teachers so that learning objectives are achieved properly. The ability to communicate in Arabic is the main goal in language because the nature of language is speech or speaking, plus the demands of the world of work today, people must be able to communicate in foreign languages, one of which is Arabic. The research model used in this research is Classroom Action Research (CAR) using a qualitative descriptive approach that aims to improve the Arabic language writing skills of tenth tenth-gradents at Madrasah Aliyah Islamic Boarding School Al Ikhlas Addary DDI Takkalas by using an Active Knowledge Sharing Strategy which has unique characteristics. other strategies do not have, namely using a list of questions with various categories including defined words. MultipMultiple-choiceions about facts or concepts ask for possible attitudes or actions. Complete sentences or match. Teachers can include some or all of the categories in making a list of questions. In accordance with the type of research chosen, namely action research, this research uses the action research model from Kemmis and Taggart, which includes planning (planning), implementation (acting), observation (observing or monitoring), and reflection (reflecting or evaluating). These four main steps form a cycle. Action research is an ongoing strategy. Learning using the Active Knowledge Sharing strategy can improve students' writing skills in class X Madrasah Aliyah Pondok Pesantren Al Ikhlas DDI Takkalasi in Arabic subjects. This is shown by the data before it is applied and after it is applied, thus answering the action hypothesis in the research that has been done that the application of the Active Knowledge Sharing strategy can improve Arabic writing skills in class X Madrasah Aliyah Pondok Pesantren Al Ikhlas Addary DDI Takkalasi Barru Regency